Zinc‐Mediated Intermolecular Reductive Radical Fluoroalkylsulfination of Unsaturated Carbon–Carbon Bonds with Fluoroalkyl Bromides and Sulfur Dioxide. Issue 7 (7th January 2019) - Liu, Yongan; Lin, Qiongzhen; Xiao, Zhiwei; Zheng, Changge; Guo, Yong; Chen, Qing‐Yun; Liu, Chao
Abstract: A versatile and general zinc‐mediated intermolecular reductive radical fluoroalkylsulfination of unsaturated C−C bonds has been developed using readily available fluoroalkyl bromides and 1, 4‐diazabicyclo[2.2.2]octane‐bis(sulfur dioxide) adduct (DABSO) with wide substrate scope and excellent functional group tolerance. Sulfur dioxide anion radical generated in situ from the reduction of sulfur dioxide with zinc may be involved in the reaction mechanism. Abstract : A zinc‐mediated intermolecular reductive radical fluoroalkylsulfination of unsaturated C−C bonds has been developed using readily available fluoroalkyl bromides, 1, 4‐diazabicyclo[2.2.2]octane‐bis(sulfur dioxide) adduct (DABSO) and N ‐fluorobenzenesulfonimide (NFSI) with wide substrate scope and excellent functional group tolerance. Sulfur dioxide anion radical generated from the reduction of sulfur dioxide with zinc may be involved in the reaction mechanism.